Density functional theory study of sulfur tolerance of copper : new copper–sulfur phase diagram - Malyi, Oleksandr I. (2013)
We study two possible mechanisms of sulfur (S) poisoning of copper (Cu) surfaces: S adsorption and formation of Cu–S compounds. Based on the performed calculations, we predict new Cu–S phase diagram that not only describes the formation of Cu–S compounds but also predicts a dependence of the transition temperature between clean and contaminated Cu surfaces on partial pressure ratio of H2 and H2S (PH2/PH2SPH2/PH2S). Since conditions under which sulfur sorbs and desorbs at Cu surfaces cannot be predicted directly from the classical thermodynamic database, our study enhances current understanding of Cu–S interaction and mechanisms of S poisoning of Cu-based catalysts.